Anglican confirmation 1945-2000: from 'the sacramental principle' to 'the challenge of baptismal unity' - Tovey, Phillip (Routledge new critical thinking in religion, theology and biblical studies, 2025)
"The focus of this book is the theology, liturgy and practice of Anglican Confirmation from 1945 to 2000. It is the third book in a series on Anglican Confirmation. The first chapters look at confirmation on a global and ecumenical level. How have questions about the place and performance of confirmation changed? Then there is a series of case studies from North America, Europe and the wider world. Two chapters are on the theology and practice of the Church of England. Attention is given to liturgical reform, theological discussion and practice including statistics. In some chapters there are case studies of individual dioceses or bishops to give snapshots of theology in action. The book uses innovative visualization techniques to present data, and uses textual network analysis to map the interrelationships of provinces at a liturgical level. The ecumenical 'baptismal unity' agenda from Vatican 2 and the World Council of Churches underlies the theological critique. This will be of great value to those in liturgical studies, church history, Anglican studies and to all bishops and clergy involved in confirmation"-- Provided by publisher